Cramming Sebagai Solusi Mahasiswa Yang Mengalami Prokrastinasi Akademik - Handayani, Nanik; Rizkya, Syiva; Azhar, Muhammad Ilham; Hassanah, Asifa Novitiara Nur; Fadesti, Pralayar Fanny (Innovative: Journal Of Social Science Research, 2024)
This study aims to determine the description of cramming in students who experience academic procrastination. This type of research is a type of qualitative research with phenomenological methods. The data collection methods used are interviews and observations. The data collection technique uses snowball sampling technique. While the data analysis technique used consists of preparing and processing data, reading the entire data, coding data, describing the results of coding into themes to be analysed, presenting themes in narrative form, and interpreting data. The results showed that the three subjects experienced academic procrastination and performed cramming behaviour. The subjects' academic procrastination was caused by several factors, either from within themselves or from the environment around them. The three subjects who experienced procrastination used the cramming method and the effect on their academic results was positive and efficient even though it had a negative impact on material understanding and health.